Harsh Parenting, Parasympathetic Activity, and Development of Delinquency and Substance Use - Hinnant, J. Benjamin (J Abnorm Psychol, 2015)
Stress response systems are thought to play an important role in the development of psychopathology. Additionally, family stress may have a significant influence on the development of stress response systems. One potential avenue of change is through alterations to thresholds for the activation of stress responses: Decreased threshold for responding may mark increased stress sensitivity. Our first aim was to evaluate the interaction between thresholds for parasympathetic nervous system (PNS) responding, operationalized as resting respiratory sinus arrhythmia (RSA), and harsh parenting in the prediction of development of delinquency and adolescent substance use (resting RSA as a biomarker of risk). The second aim was to evaluate if resting RSA changes over time as a function of harsh parenting and stress reactivity indexed by RSA withdrawal (altered threshold for stress responding). Our third aim was to evaluate the moderating role of sex in these relations. We used longitudinal data from 251 children ages 8 to 16. Mother-reports of child delinquency and RSA were acquired at all ages. Adolescents self-reported substance use at age 16. Family stress was assessed with child-reported harsh parenting. Controlling for marital conflict and change over time in harsh parenting, lower resting RSA predicted increases in delinquency and increased likelihood of drug use in contexts of harsh parenting, especially for boys. Harsh parenting was associated with declining resting RSA for children who exhibited greater RSA withdrawal to stress. Findings support resting PNS activity as a moderator of developmental risk that can be altered over time.